1997
DOI: 10.1097/00006123-199707000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Chemotherapy with Carmustine-loaded Polymers for High-grade Gliomas: A Randomized Double-blind Study

Abstract: Carmustine applied locally in a biodegradable polymer at the time of primary operation, seems to have a favorable effect on the life span of patients with high-grade gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
219
0
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(228 citation statements)
references
References 11 publications
4
219
0
5
Order By: Relevance
“…With respect to additional data on the benefit of local chemotherapy, 2 previous placebo-controlled, doubleblind studies of BCNU wafers in malignant glioma have been conducted (Brem et al, 1995;Valtonen et al, 1997). In all 3 studies, BCNU wafers have shown a survival benefit compared to placebo wafers, with a mortality risk reduction of 31% (Brem et al in recurrent malignant glioma), 63% (Valtonen et al in primary malignant glioma), and 29% (the present study).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…With respect to additional data on the benefit of local chemotherapy, 2 previous placebo-controlled, doubleblind studies of BCNU wafers in malignant glioma have been conducted (Brem et al, 1995;Valtonen et al, 1997). In all 3 studies, BCNU wafers have shown a survival benefit compared to placebo wafers, with a mortality risk reduction of 31% (Brem et al in recurrent malignant glioma), 63% (Valtonen et al in primary malignant glioma), and 29% (the present study).…”
Section: Discussionmentioning
confidence: 59%
“…In an initial small study of patients (N = 32) with primary malignant glioma, BCNU wafer-treated patients (n = 16) had a median survival of 13.4 months vs. 9.2 months for the placebo wafer-treated patients (n = 16). The BCNU wafer-treated patients had significantly improved 12-month and overall survival compared to placebo wafer-treated patients (Valtonen et al, 1997).…”
mentioning
confidence: 86%
“…Biodegradable controlled-release polymers loaded with carmustine have been established as a safe and effective therapy for patients with malignant gliomas (8)(9)(10)(11)(12). Given the inherent advantages of locally-delivered chemotherapy, there has been continued interest in the development of additional controlled-release drug delivery systems suitable for intraparenchymal administration of novel antineoplastic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of biodegradable polymers that release chemotherapeutic agents directly into the tumor has proved to be a promising strategy at increasing the local delivery of the drug. Nitrosoureas, including BCNU, are a class of chemotherapeutic agents that have been incorporated into biodegradable polymers and, upon intracranial implantation, have demonstrated efficacy in phase III clinical trials in patients with both recurrent and newly diagnosed malignant gliomas [3,36,40]. Importantly, in contrast to systemic administration of nitrosoureas, this treatment has not been associated with systemic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Since most gliomas recur within 2 cm of the original tumor site [14,18], this anti-tumor strategy has the potential to control both local recurrence and improve overall survival. This approach has been evaluated in Phase III clinical trials with the nitrosourea, carmustine (BCNU) and has demonstrated significant improvement in survival in patients with malignant gliomas both at recurrence and at initial presentation [3,36,40].…”
Section: Introductionmentioning
confidence: 99%